Automated mobility transitions: governing processes in the UK - Hopkins, DM; Schwanen, T (MDPI, 2018)
Contemporary systems of mobility are undergoing a transition towards automation. In the UK, this transition is being led by (often new) partnerships between incumbent manufacturers and new entrants, in collaboration with national governments, local/ regional councils, and research institutions. This paper first offers a framework for analyzing the governance of the transition, adapting ideas from the Transitions Management (TM) perspective, and then applies the framework to ongoing automated vehicle transition dynamics in the UK. The empirical analysis suggests that the UK has adopted a reasonably comprehensive approach to the governing of automated vehicle innovation but that this approach cannot be characterized as sufficiently inclusive, democratic, diverse and open. The lack of inclusivity, democracy, diversity and openness is symptomatic of the post-political character of how the UK’s automated mobility transition is being governed. The paper ends with a call for a reconfiguration of the automated vehicle transition in the UK and beyond, so that much more space is created for dissent and for reflexive and comprehensive big picture thinking on (automated) mobility futures.